Art, Politics and the Pamphleteer. - Tormey, Jane (Bloomsbury Publishing Plc, 2020)
"Art, Politics and the Pamphleteer brings together a collection of text-based and visual essays, commissioned artworks and graphics. This richly illustrated book responds to the concept, aesthetics and function of the political pamphlet. It is diverse in content, interpreting the 'pamphlet' in the broadest terms, and encompassing a number of case studies that offer historical or specific examples of contemporary pamphleteering practice that can be seen to perform 'a clear political implication' or protest. Besides exploring the radical history and diverse cultures of the pamphlet, it also celebrates the rich visual rhetoric, typography and contemporary relevance of the format for both artists and activists. Contributions include an historical overview and essays by: Andy Abbott, Angeliki Avgitidu, Aziz Choudry and Dširě Rochat, David Murrieta Flores, Michelle Kempson, Pil and Galia Kollectiv, Rachel Schreiber, Jane Tormey, Gillian Whiteley; visual contributions by Gary Anderson and Steven Shakespeare, Ruth Beale, Ami Clarke, Common Culture, Jeremy Deller, Freee, Patrick Goddard, Gavin Grindon, Ferenc Grof, Marc Herbst, Joanne Lee, Josh MacPhee, Manual Labours, Mark McGowan, Minute Works, Chris Morton, radicalreThink, Hester Reeve, Oliver Ressler, Greg Sholette & Christopher Darling, Laura Wild, Andrew Wilson. As the book was conceived as predominantly visual from the outset, the book concept has been a collaboration with The Little Riot Press (Phil Eastwood and Chris Dunne). Overall, an aesthetic of protest and propaganda was considered integral to the design to reiterate the generally handmade, analogue techniques found in political pamphlets. The Little Riot Press have thus approached the illustration and overall visual cohesion from the perspective of the radical artist pamphleteer. www.thelittleriotpress.com."-- Provided by publisher.
Description based upon print version of record.
'FANM VLE PALE': HAITIAN MIGRANT WOMEN'S VOICES IN QUEBEC.
Keywords: Pamphlets -- Design.; Political posters -- Design.; Art and state -- History.; Propaganda -- History.; Brochures -- Mise en pages.; Art -- Politique gouvernementale -- Histoire.; Propagande -- Histoire.; Social & cultural history.; Art -- Art & Politics.; Philosophy -- Aesthetics.; Philosophy -- Political.; Art and state; Pamphlets -- Design; Propaganda; History